THE RELATIONSHIP BETWEEN HOUSEHOLD ENVIRONMENTAL SANITATION AND THE INCIDENCE OF DENGUE HEMORRHAGIC FEVER IN THE WORKING AREAS OF MUTIARA TIMUR HEALTH CENTER AND PIDIE HEALTH CENTER, PIDIE REGENCY - Nurzhri, Andi; Adamy, Aulina; Andria, Dedi (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2025)
Background: The incidence of Dengue Hemorrhagic Fever (DHF) in Indonesia, including Pidie District, has shown significant year-to-year variation. Mutiara Timur Public Health Center recorded 66 DHF cases in 2015, 29 cases in 2016, and 75 cases in 2017, while Pidie Public Health Center reported 15 cases in 2015, 29 cases in 2016, and 16 cases in 2017. Method: This study employed a cross-sectional design with a population of 226 individuals, selected using proportional random sampling, resulting in a total of 72 respondents. Data were collected through interviews, observations, and documentation from August 12 to 19, 2019. The data were analyzed using univariate and bivariate methods with the Chi-square test. Result: The analysis showed no significant relationship between housing density (P Value: 0.082), dark rooms in the house (P Value: 0.380), and house ventilation (P Value: 0.507) with the incidence of DHF. Recommendation: The study suggests the need to enhance public knowledge about DHF as a risk factor and highlights the importance of implementing the 3M (Drain, Cover, Bury) and 3M Plus (Avoid mosquito bites) programs for disease prevention.